2010
DOI: 10.1590/s1519-69842010005000003
|View full text |Cite
|
Sign up to set email alerts
|

Responses of freshwater molluscs to environmental factors in Southern Brazil wetlands

Abstract: Freshwater molluscs play an important role in aquatic ecosystems, providing food for many fish species and vertebrates. Investigations on factors that determine mollusc species richness and distribution in wetland systems are scarce in the Neotropical region. The main goal of this study was to determine how much variation in mollusc richness and composition is explained by area, hydroperiod, altitude, water conductivity, and dominant aquatic vegetation. This survey was performed in an extensive area of a Neotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
0
16
0
5
Order By: Relevance
“…Because the temperature of the air and the concentration of dissolved solids contained redundant information (inflation factors >20), these parameters were not considered in the analysis (Ter Braak, 1986;Ter Braak and Verdonschot, 1995;Külköylüoğlu, 2003;2005;Külköylüoğlu and Dügel, 2004;Maltchik et al,2010). The mean value of each environmental variable together with data on the species abundance from eight sampling stations were used in the CCA (Kovach, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Because the temperature of the air and the concentration of dissolved solids contained redundant information (inflation factors >20), these parameters were not considered in the analysis (Ter Braak, 1986;Ter Braak and Verdonschot, 1995;Külköylüoğlu, 2003;2005;Külköylüoğlu and Dügel, 2004;Maltchik et al,2010). The mean value of each environmental variable together with data on the species abundance from eight sampling stations were used in the CCA (Kovach, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…In southern Brazil, Mansur et al (1991) and Pereira et al (2000) recorded, respectively, 13 native bivalve species (nine occurring in lakes and 11 in lotic environments) and 19 species, of which only six occurred in lentic environments such as those of the present study. Maltchik et al (2010) recorded only bivalve's species of the Sphaeriidae for wetlands of this region. Our results indicate that the structure of the bivalve assemblages in the lakes of the Cuiabá floodplain was determined by characteristics of the bottom and that there was an interaction between the factors of organic matter and sediment granulometry, which confirms some of the findings reported by other authors (Strayer, 1993;Layzer and Madison, 1995;McRae et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…The variables of ecological importance in the substratum include the physical structure (granulometric composition), organic content, stability and heterogeneity (Callisto and Esteves, 1996). Factors such as dissolved oxygen, hydrogen potential (pH) (McMahon, 1991), water conductivity and hydroperiod (Maltchik et al, 2010) may also be involved in the distribution of bivalves. The limitation of many bivalves to shallow habitats, when in lentic waters, is related to their low tolerance to hypoxia (Burky, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have revealed toxicity of most substances is affected by such factors as DO, water hardness and pH (Økland, 1990;Duft et al 2007). The comparative studies in aquatic molluscs have revealed that species' distributions are restricted by environmental conditions (Hunter, 1961;Økland, 1969;Dussart, 1976, Dillon, 2000Maltchik et al 2010;Zeybek et al 2012). As some are edible, many being agricultural pests or hosts to parasitic organisms, they have parasitological importance (Şeşen and Yıldırım.…”
Section: Introductionmentioning
confidence: 99%